Pengaruh Model SETS Terhadap Pola Berpikir Kritis Siswa Pada Pembelajaran IPA Di SD - Zahdinny Mucharina Fadhillah; Candra Listi Rahmani; Mabda Arqomah; Nur Ngazizah (Indonesian Publication Center, 2024)
This study aims to analyze the implementation of the Science, Environment, Technology, and Society (SETS) model in improving the quality of science learning. The study employed a qualitative descriptive method with a case study design. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that science learning using the SETS model has not been optimally integrated, especially in connecting aspects of science, environment, technology, and society. However, the application of the SETS model following its principles successfully improved students’ understanding of the material. Students became more active, creative, and capable of critical thinking by linking events to SETS elements. Furthermore, this model increased students’ learning interest through interactive activities, differing from traditional lecture methods. Although the results demonstrated positive impacts, implementing the SETS model requires further optimization to achieve full integration between its elements. This study concludes that the SETS model holds significant potential in enhancing the quality of science learning in elementary schools, particularly in terms of material comprehension, critical thinking skills, and students’ learning interest.